Da li se kasni sa uvođenjem insulinske terapije kod bolesnika sa dijabetesom tip 2 u kliničkoj praksi? - Antić, Slobodan (Acta medicae Medianae, 2020)
Introduction: Adequate time to start insulin therapy implies when treatment of hyperglycemia is not achieved. The reasons for the delay in starting insulin therapy may be due to certain doubts that are present in patients, but also to the doctor. Aims: To investigate conditions of the patients at the time of the introduction of insulin therapy in patients with type 2 diabetes and what was the condition of patients 6 months prior to the introduction of insulin therapy Material and methods: The study included 70 patients with type 2 diabetes, introduced to insulin therapy. The study involved an analysis of the anamnesis and clinical data according to the study protocol, and 6 months before the introduction of insulin therapy, and just before the introduction of insulin therapy. Results: At the time of the introduction to insulin therapy, glucose values ​​were 12.02 ± 2.54, and six months earlier values ​​were 12.18 ± 2.99. HbA1c values ​​at the time of the introduction to insulin amounted to 10.88 ± 1.65, and six months before 10.02 ± 1.67. The values ​​of BMI at the time of the introduction to insulin therapy were 28.90 ± 7:54, and six months before 28.23 ± 5.79. Conclusion: there is deley in the initiation of insulin therapy with type 2 diabetes patients. Insulin therapy leads to improvement of glycemic control and significant reduction in HbA1c.